Lexical and Semantic Constraints in Compiling a Bilingual Dictionary from Tribal Language to English - Bhatt, Disha; Pattnaik, Minushree; Sarangi, Itishri (International Journal of Psychosocial Rehabilitation, 2019)
Dictionary compiling is one of the most challenging tasks for Lexicographers. They have to focus on both logical and lexical semantics during the process of compiling the dictionary. The logical semantics includes sense, reference, presupposition and implication side of language whereas lexical semantics includes analysis of word meanings and relations between them. A good lexicographer strives to create a balance between logical and lexical semantics in order to compile a dictionary. The intensity of the challenge is mild in the case of monolingual dictionary but it shoots up when we have to compile a bilingual/trilingual dictionary. The reason behind this is that the differences in socio-cultural background come into the picture. The meaning of a word may differ because it varies from context to context, hence just jotting down literal meanings while compiling the dictionary may not solve the purpose. If we want to popularise tribal language then we have to produce a bilingual dictionary which will include English language. Compiling a dictionary from tribal language to English is a challenge because English is not the native language of the tribal community and in maximum cases the translator and lexicographer both are neither native speakers of that particular tribal language nor English. It is true that tribal language to English dictionary has been compiled but the credibility is at stake.